Crystallization kinetics as a tool to fine-tune the catalytic activity of Na-LTA zeolite precursors in the transesterification of glycerol to glycerol carbonate - Zapelini, Iago William [UNESP]; de Paula, Gustavo Medeiros; Cardoso, Dilson (Elsevier, 2025)
Glycerol carbonate is a versatile molecule used as a fuel additive and a chemical building block. It is a prominent route for glycerol valorization, improving the biodiesel production chain. This base-catalyzed reaction can be carried out using sodium-type zeolites if accessibility to the basic sites is ensured. Herein, we report a facile strategy to fine-tune the number and access to basic sites of Na-LTA zeolite precursors via monitoring the crystallization kinetics of the microporous material. It is demonstrated that an optimal glycerol to glycerol carbonate conversion is obtained when using the solid obtained at the beginning of the crystallization (90 min at 100 °C of hydrothermal step). Textural and spectroscopy characterization reveals that semicrystalline material presents many basic aluminate anions in a very open structure, allowing facile access to glycerol and propylene carbonate. Moreover, it is shown that this catalyst is stable in four successive reaction cycles and active in different reactions conditions
Keywords: Accessibility; Aluminate; Basicity; Biomass; Crystal growth